THE DEVELOPMENT OF ETHNO-STEM INTEGRATED E-LKPD ON REACTION RATE MATERIALS - Elfany, Yuna; Sudrajat, Ajat (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This development research was conducted because the advancement of education in the 21st century is geared towards improving human potential. The shift of global society towards digitalization forces schools to adapt their teaching methods to new technological advances. This study aims to determine the analysis of students' needs, the level of feasibility, teacher practicality, and students' readability response to the Ethno-STEM integrated LKPD on reaction rate material. The method used is research and development (Research and Development) with the 4-D model, but limited to 3-D (Define, Design, and Develop). The research subjects were 3 material and media validators, 5 chemistry teachers and 90 students of SMA Negeri 1 Kisaran. The data collection techniques used were interviews and questionnaires. The data were analyzed using kappa moment. Based on the results of the study, students need Ethno-STEM integrated E-LKPD on reaction rate material, the material feasibility level is 0.84 (very feasible), the media feasibility level is 0.85 (very feasible), the practicality level is 0.95 (very practical), and the results of students' readability response are 0.90 (very good). Keyword: E-LKPD; Ethno-STEM; Reaction Rate. Abstrak: Penelitian pengembangan ini dilakukan karena kemajuan pendidikan di abad ke-21 diarahkan untuk meningkatkan potensi manusia. Pergeseran masyarakat global ke arah digitalisasi memaksa sekolah untuk menyesuaikan metode pengajaran mereka dengan kemajuan teknologi baru. Penelitian ini bertujuan untuk mengetahui analisis kebutuhan peserta didik, tingkat kelayakan, kepraktisan guru, dan respon keterbacaan peserta didik terhadap LKPD terintegrasi Ethno-STEM pada materi laju reaksi. Metode yang digunakan adalah penelitian dan pengembangan (Research and Development) dengan model 4-D, namun dibatasi hingga 3-D (Define, Design, dan Develop). Subjek penelitian adalah 3 orang validator materi dan media, 5 orang guru kimia dan 90 orang peserta didik SMA Negeri 1 Kisaran. Teknik pengumpulan data yang digunakan adalah wawancara dan kuesioner. Data dianalisis dengan menggunakan momen kappa. Berdasarkan hasil penelitian, peserta didik membutuhkan E-LKPD terintegrasi Ethno-STEM pada materi laju reaksi, tingkat kelayakan materi sebesar 0,84 (sangat layak), tingkat kelayakan media sebesar 0,85 (sangat layak), tingkat kepraktisan sebesar 0,95 (sangat praktis), dan hasil respon keterbacaan peserta didik sebesar 0,90 (sangat baik). Kata kunci: E-LKPD; Etno-STEM; Laju Reaksi.